Junto e misturado: imanência e transcendência no PCC - Biondi, Karina (Universidade Federal de São Carlos, 2009)
The Primeiro Comando da Capital (PCC), a collectivity originated inside prisons in the state of São Paulo in the early 1990s, underwent deep transformations with the addition of Equality to its ideals. The incorporation of this principle has instituted a tension that infiltrates and runs through the capillaries of the PCC, effecting simultaneous formations and suppressions of power foci, alongside concurrent constructions and dissolutions of hierarchies. A series of mechanisms and strategies have been triggered in order to set up a Command between equals , establishing tensions in all its political dimensions. This work approaches the functioning of the PCC through the description of diverse plans by which its politics is operated. One of these plans concerns the PCC as a transcendental force, whose investigation led to theoretical wrings that enabled me to reflect about the construction of a transcendence by means of an immanentist anthropology, that is, an anthropology that allows the understanding of transcendence and the means of its production without considering it preeminent. It is the PCC-transcendence, produced in the immanence and to it mingled, that allows successive processes of deterritorialization concomitant to desindividualization phenomena, and supports the existence of this social formation without a firm territorial link, enabling the presence of the PCC even where we do not find its members.
Keywords: Antropologia política; Primeiro Comando da Capital; Prisioneiros; Micropolítica; CIENCIAS HUMANAS::ANTROPOLOGIA